Resepsi Masyarakat Kota Manado terhadap Quick Response Code Indonesian Standard (QRIS) dalam Melakukan Transaksi - Adyantana Yusuf Sidiq; Rosdalina Bukido (Kunuz: Journal of Islamic Banking and Finance, 2023)
This study aims to investigate public understanding of the Quick Response Code Indonesian Standard (QRIS) as a digital payment method. In Indonesia, the digitization of the payment system has experienced rapid progress and has received high interest from the public. Digital-based payment methods, especially QRIS, have become a favorite among the public. This study uses a descriptive qualitative research method. The results of the study show that people's understanding of QRIS payments in buying and selling transactions, issued by Bank Indonesia together with ASPI (Indonesian Payment System Association), is good. The informants in this study understand that QRIS is a digital payment method using a barcode that makes it easier for people to make transactions. This understanding is reflected in the results of interviews with the seven informants, which indicated that they understood QRIS as a service or payment method using a barcode through digital wallet and m-banking applications. This payment method makes it easy for people to make transactions. Thus, this study shows that the public has a good understanding of QRIS as a digital payment method. QRIS provides convenience and comfort in transactions for the community.